Onde estão as crianças com deficiência motora em Sergipe? Tensionando a saúde e a educação - Souza, Laila Bianca Menezes (2024)
Inclusive Education is the result of political and social achievements, as well as an understanding of a social model of disability and differences. Children and adolescents with motor disabilities face various obstacles to accessing and remaining in school. Considering the context of special education in the state of Sergipe, and the different dimensions involving each target audience, this study aimed to understand the educational journey of children and adolescents with motor disabilities in Sergipe. Methodologically, it is grounded in collaborative-critical action research and constitutes a descriptive exploratory study of a quantitative-qualitative nature. The process involved: application of the semi-structured "School and Communicational Screening" questionnaire with families of children with motor disabilities served by the Specialized Rehabilitation Center José Leonel Ferreira Aquino (CER IV) in Aracaju/SE; intervention with Alternative Communication and the use of an eye-tracking device; and a dialogical meeting with mothers. Thirty-seven questionnaires were administered in person to mothers of children and adolescents with motor disabilities, and interventions were conducted with 3 children/adolescents—2 received 3 sessions each, and 1 received 6 sessions. The investigation yielded the following results: 1) Out of 37 children, 12 do not attend or have never attended school, citing the lack of a caregiver as the main reason. Among the 25 enrolled children, 23 attend school. Of these 23, only 3 are placed exclusively in the Specialized Educational Assistance Room. Among the remaining 20, only 3 attend school every day, 4 attend four times a week, 7 attend three times a week, 5 attend twice a week, and 1 attends once a week. 2) Communication profiles were found to be crucial for the child's presence in school and the type of work performed. It was observed that the 3 children attending school daily are those who can communicate verbally, whereas those with partially intelligible, unintelligible speech, or without speech attend school less frequently. 3) Motor and communication profiles indicated that medium and high-tech resources are recommended for alternative communication for many of these children, while the socio-economic reality of families significantly affects their access to these resources. 4) All 3 children selected to begin using Alternative Communication with high-tech devices showed good progress with the device. 5) Mothers reported multiple factors hindering their children's effective participation in school, and after the eye-tracking intervention, they expressed higher expectations for their children's communication and learning development.In conclusion, children with motor disabilities are receiving healthcare support, with education taking a back seat, highlighting the need for better coordination between health and education sectors to prevent overlap. Moreover, it was found that despite speech difficulties or absence, alternative communication systems are not being offered to this population, with the majority needing high-tech Alternative Communication systems. This underscores the urgent need to advance towards building a public school system that is democratic, inclusive, and accessible to all.